Bacteroides fragilis ameliorates Cronobacter malonaticus lipopolysaccharide-induced pathological injury through modulation of the intestinal microbiota - Ling, Na; Zhang, Xiyan; Forsythe, Stephen; Zhang, Danfeng; Shen, Yizhong; Zhang, Jumei; Ding, Yu; Wang, Juan; Wu, Qingping; Ye, Yingwang (Frontiers in Immunology, 2022)
Cronobacter has attracted considerable attention due to its association with meningitis and necrotizing enterocolitis (NEC) in newborns. Lipopolysaccharide (LPS) normally facilitates bacterial translocation along with inflammatory response as an endotoxin, however, the pathogenicity of Cronobacter LPS and alleviation strategies to the toxicity were largely unknown. In this study, inflammatory responses were stimulated by intraperitoneal injection of C. malonaticus LPS into Sprague Dawley young rats. Simultaneously, B. fragilis NCTC9343 were continuously fed through gavage for 5 days before or after injection of C. malonaticus LPS to evaluate the intervention effect of B. fragilis. We detected morphological changes of ileum and colon, intestinal microbiota, production of inflammatory factors including tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and interleukin-10 (IL-10), and expression abundance of Toll-like receptor 4 (TLR4), occludin, claudin-4, and iNOs. The results indicated that C. malonaticus LPS exacerbated intestinal infection by altering gut microbe profile and expression of tight junction proteins, and releasing inflammatory factors in a time- and dose-dependent manner. Intriguingly, B. fragilis treatment obviously diminished the pathological injuries and expression of TLR4 caused by C. malonaticus LPS, and increased gut microbe like Prevotella-9. We note that Shigella, Peptoclostridium, and Sutterella might be positively related to C. malonaticus LPS infection, but Prevotella-9 was negatively correlated. These data suggested that intestinal microbiota is an important target for precaution and treatment of pathogenic injuries induced by C. malonaticus LPS.